Impact of FGFR2 gene fusions on survival of patients with intrahepatic cholangiocarcinoma following curative intent resection. Issue 10 (October 2022) - Buckarma, EeeLN; De La Cruz, Gabriel; Truty, Mark; Nagorney, David; Cleary, Sean; Kendrick, Michael; Borad, Mitesh; Graham, Rondell P.; Gores, Gregory; Smoot, Rory
Abstract: Background: Intrahepatic Cholangiocarcinoma (iCCA) is an aggressive cancer with diverse mutational profiles. An important molecular subtype is fibroblast growth factor receptor 2 (FGFR2) fusion. The effect of FGFR2 fusions on prognosis is unknown. Our aim was to assess the outcomes in resected CCA patients in relation to FGFR2 status. Methods: Surgically treated CCA patients from a single institution were retrospectively reviewed between 2008 and 2014. FGFR rearrangements were detected by fluorescence in situ hybridization (FISH). Data included patient demographics, tumor pathology, disease-free survival (DFS) and overall survival (OS). Results: Ninety-five patients underwent surgical resection for iCCA. Twelve (13%) of these were found to have FGFR2 fusion, none of which were treated with FGFR targeted therapy. Patients with FGFR2 fusions were found to have a longer 5-year (83 vs. 32%, p = 0.01) and 10-year (46 vs. 22%, p = 0.04) OS. Five and 10-year DFS was also increased (68 vs. 33% p = 0.04) and (68 vs. 25 %, p = 0.02, ). FGFR2 fusion status was the strongest independent factor associated with improved OS (HR 0.23, 0.09–0.62, p=0.003) and DFS (HR 0.18, 0.05–0.67, p=0.01). Conclusion: Patients with CCA FGFR2 fusion have improved OS and DFS following surgical resection.